Development of waxy Cassava with different biological and physico-chemical characteristics of starches for industrial applications - Zhao, SS; Dufour, D.L.; Sánchez, T.; Ceballos, H.; Zhang, P. (Wiley, 2011)
The quality of cassava starch, an important trait in cassava breeding programs, determines its applications in various industries. For example, development of waxy (having a low level of amylose) cassava is in demand. Amylose is synthesized by granule-bound starch synthase I (GBSSI) in plants, and therefore, down-regulation of GBSSI expression in cassava might lead to reduced amylose content. We produced 63 transgenic cassava plant lines that express hair-pin dsRNAs homologous to the cassava GBSSI conserved region under the control of the vascular-specific promoter p54/1.0 from cassava (p54/1.0